Application of fuzzy logic for the determination of the quality of bodies of water in the rimac river watershed - Aguirre, A. (2017)
The purpose of the present work is to determine the quality of five bodies of water within the Rimac river watershed, by analyzing the data provided by the Autoridad Nacional del Agua (ANA ‐ the National Water Authority) in its report on Technical Monitoring of Water Quality in the Rimac River Watershed (2013). These five bodies of water have been assigned to Category 1 A2 ("Domestic and Recreational Use") indicating that their water could be made potable through conventional treatment. The results can be used as a tool to evaluate the quality of bodies of water and facilitate their environmental management, by identifying those would be more prone to lose their qualification as Category 1 A2. Use of the Grey Clustering Analysis methodology and the Prati water quality index allowed us to carry out the analysis in an objective manner. The criteria for selecting the bodies of water was the proximity of their monitoring point to the Rimac river (downstream), because of their importance as a point of convergence of all the contaminants [1] that could be brought from upstream. It was found that the five bodies of water in consideration were not contaminated, so that they do belong to Category 1 A2. This means that they do not represent any risk for human health and can be made potable through conventional water treatment.